IDNLearn.com makes it easy to find the right answers to your questions. Our community is ready to provide in-depth answers and practical solutions to any questions you may have.
The equation given is:
[tex]\frac{1}{4}(\frac{1}{3}k+9)=6[/tex]Multiply both-side of the equation by 6
[tex]4\times\frac{1}{4}(\frac{1}{3}k+9)=6\times4[/tex][tex](\frac{1}{3}k+9)=24[/tex]subtract 9 from both-side of the equation
[tex]\frac{1}{3}k=15[/tex]To get k, we are to multiply both-side of the equation
[tex]k=45[/tex]Therefore, Olga made a mistake in the last step